U-series disequilibria generated by partial melting of spinel lherzolite - Landwehr, D; Blundy, J; Chamorro-Perez, E; Hill, E; Wood, B (2001)
We have experimentally investigated the effects of crystal chemistry on the partitioning of U and Th between clinopyroxene and anhydrous silicate melt in a wide range of synthetic systems from 1 to 8 GPa and 1330 to 1735°C. We have also generated limited additional data for garnet-melt and pigeonite-melt U-Th partitioning. We find that for sub-calcic clinopyroxenes, of the variety which characterise the mantle solidus, DU is greater than DTh, as previously predicted from theoretical considerations based on the size of the M2 site into which substitution occurs. Melt composition appears to have a minor effect on partitioning.The new partitioning data have been combined with existing experimental data to derive a thermodynamically based expression that predicts DTh and DU from crystal chemistry, pressure and temperature. This model has been combined with published experimental determinations of clinopyroxene composition along the mantle solidus to derive the variation in DTh and DU/DTh during mantle melting. A simple, one-dimensional model dynamic mantle melting using the new data shows that 230Th excesses, expressed as the activity ratio (230Th/238U), of up to 1.34 can be generated within the spinel lherzolite stability field. This value is in excellent agreement with the maximum 230Th excess (1.35) observed in mid-ocean ridge basalt (MORB). The magnitude of excess correlates linearly with the depth to the onset of melting. These findings, which are relatively insensitive to plausible variations in mantle porosity and melt productivity, are consistent with observed global variations in MORB 230Th excesses with ridge axial depth. We conclude that significant 230Th excess can be generated by melting of spinel lherzolite, in the absence of garnet. © 2001 Published by Elsevier Science B.V.